Measuring of main performance indicators of IKU-EKO UNJA Smart at IKU 2 students get off-campus experience through academic scorecards - Arpizal Arpizal; Iwan Putra; Nurmala Sari; Novia Sri Dwijayanti; Ahmad Nasori (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
In an effort to oversee the achievement of UNJA's vision to become a World Class Entrepreneurship University, especially in the next 5 years, it has been outlined in the 2020-2024 UNJA SMART Strategic Plan concerning UNJA SMART principles, objectives, strategic plans and improvement of Key Performance Indicator Items, especially IKU 2 Study Abroad Experience Campus. The method used in Measuring the Digital Platform IKU-EKO UNJA SMART at IKU 2 Students Get Experience Off-Campus (One Lecture, One Book, And One Blended) namely with Academic Scorecards. The samples in this study were 92 Study Programs at the University of Jambi. From the results of the activities carried out, it can be concluded that there is a need for a reliable, comprehensive, coherent, measurable, and balanced performance measurement system at UNJA, such as performance measurement using the Academic Scorecard model, especially in fulfilling the Students IKU 2. The implication of this research is to produce a Blue Print for UNJA SMART IKU-EKO measurement using KPI derived from Rensta through academic scorecards with the hope that synergy can be carried out in integrating organizational strategy with organizational performance.